The relationship between technology acceptance model and intentıon to purchase online : The moderating effect of cultural differences - Marolt, Tara (My University, 2024)
Bu çalışmanın amacı Sloven ve Türk tüketicilerde Teknoloji Kabul Modeli ve çevrimiçi satın alma niyetini, kültürün modeli nasıl etkilediğini ve tüketiciler arasındaki farklılıkları araştırmaktır. Anket, 6 puanlık aralık ölçeği ile ölçülen iki bölümden oluşan 26 içerik sorusundan oluşmaktadır. Anket Türk ve Sloven tüketicilere dağıtıldı ve 308 uygun yanıt toplandı. Slovence anketinin algılanan kullanışlılık, algılanan kullanım kolaylığı ve niyet ölçekleri Brezavšček, Šparl ve Žnidaršič (2014)'ten (Hsu, Wang ve Chiu 2009'dan uyarlanmıştır) uyarlanmıştır. Hsu, Wang ve Chiu (2009) maddeleri. Tutum ölçeği Slovenya örneklemi için Krajnc (2018), Türkiye örneklemi için ise Šebjan, Tominc ve Yıldırım (2017)'dan uyarlanmıştır. Son olarak bireycilik/ toplulukçuluk ve erkeklik/ dişillik ölçeği Sloven örneklemi için Pfajfar (2012) ve Türkiye örneklemi için Saylık (2019)'dan uyarlanmıştır. Sonuçlar, algılanan kullanışlılık ile tutum arasındaki ilişkide tek anlamlı düzenleyici değişkenin erkeklik/ kadınlık olduğunu, bireysellik/ toplulukçuluğun ise her iki örnekte de önemsiz olduğunu gösterdi. Teknoloji Kabul Modelindeki değişkenler arasındaki diğer ilişkilerin (algılanan kullanışlılık, algılanan kullanım kolaylığı, tutum ve satın alma niyeti) her iki örnekte de anlamlı derecede pozitif olduğu ortaya çıktı, ancak iki grup arasında önemli farklılıklar bulundu.

The purpose of this study was to research Technology Acceptance Model and intention to purchase online in Slovenian and Turkish consumers and how culture affects the model and the differences between the consumers. The questionnaire consists of 26 content questions in two parts measured with a 6 point interval scale. Questionnaire has been distributed to Turkish and Slovenian consumers, and 308 suitable responses were collected. Perceived usefulness, perceived ease of use and intention scales for Slovenian questionnaire were adapted from Brezavšček, Šparl and Žnidaršič (2014) (who adapted it from Hsu, Wang, and Chiu 2009), Turkish version of the scales was done by translation and adaptation of Hsu, Wang, and Chiu (2009) items. Attitude scale was adapted from Krajnc (2018), for Slovenian sample, and Šebjan, Tominc and Yıldırım (2017) for Turkish sample. Lastly scale for individualism/ collectivism and masculinity/ femininity were adapted from Pfajfar (2012), for Slovenian sample and, and Saylık (2019) for Turkish sample. The results showed that the only significant moderating variable was masculinity/ femininity on the relationship between perceived usefulness and attitude, while individualism/ collectivism was insignificant in both samples. The other relationships between variables from the Technology Acceptance Model (perceived usefulness, perceived ease of use, attitude and intention to purchase) turned out to all be significantly positive in both samples, but significant differences were found between the two groups.
Kültürel farklılığın teknoloji kabul modeli ile çevirimiçi satın alma niyeti arasındaki düzenleyici etkisi
Keywords: Consumer behavior; Culture; Intention to Purchase; Kültür; Marketing; Pazarlama; Psikolojik yönler; Psychological aspects; Satın Alma Niyeti; Social media; Sosyal medya; Technology acceptance model; Teknoloji kabul modeli; Tüketici davranışı